Compliance to South African Auditor General's audit recommendations: a case study - Sanyane F. Kgobe; Modupi Selepe (Insights into Regional Development)
The current state of local government has reached a crisis point, marked by escalating financial distress and persistent poor financial governance outcomes. Across South Africa, municipalities are grappling with economic instability. There are exacerbating concerns regarding the effective management of public resources. Empirical studies and municipal audit reports have shed light on the pervasive nature of this crisis, revealing a troubling pattern of irregularities and weaknesses that persist from year to year. Despite various measures, such as the Local Government Turnaround Strategy, there continues to be a need for more compliance enforcement, perpetuating a cycle of recurring challenges. The purpose was to determine the extent to which local municipalities in the Waterberg District Municipality, Limpopo Province, South Africa, have implemented and complied with the recommendations of the AGSA. Methodologically, a qualitative approach was used, drawing from various primary and secondary data sources. A thorough literature review was done to determine how closely municipalities follow the AGSA's annual audit recommendations. The primary conclusions indicated that internal factors, including inadequate financial management procedures, a shortage of time and resources, staffing issues, and political meddling, were to blame for the municipalities' unfavourable audit opinions. Furthermore, there remains a mix of sentiments regarding the implementation of AGSAs, even though most municipalities follow the AG's recommendations. The study suggests several practical approaches to address these issues, including creating a unit for monitoring and evaluation, putting internal solid control measures in place, implementing consequences management, implementing an effective system for managing records, and performing skills audits.